“I have forgotten your love, yet I seem to glimpse you in every window”: The Hermeneutical Aesthetics of (Be)longing - Małgorzata Hołda (Text Matters)
The article addresses the nuanced but also profoundly enticing and challenging reality of belonging evoked in painting. I examine three artworks by artists of different times and styles—John Everett Millais, Johannes Vermeer, and Salvador Dalí—to show how art facilitates our understanding of the phenomenon of human belonging. The selected works of art are connected via the motif of a female figure in front of a window, as well as the implicit or apparent theme of love. Focusing on the motif of the window, which represents both a literal and metaphorical barrier but also a gateway to what is unknown and unfamiliar, I seek to discover the diverse and unexpected understandings of the phenomenon of belonging, viewed in the light of either an overt or implied intimate relationship. The aesthetic encounter with these artworks offers a unique possibility to uncover the uncharted territories of our sense of belonging. As a theoretical backdrop, I follow the precepts of Hans-Georg Gadamer’s ontology of art. Gadamer claims that the artwork’s meaning comes to its full realization in the aesthetic encounter; he names that which happens—an increase in being—Zuwachs an Sein. The increase in being relates to the inexhaustible meanings that shine forth while we are contemplating an artwork. The aesthetic intimations of the paintings under scrutiny bring to light the subtle senses of the interweaving of dwelling, longing, belonging, and love.